2020
DOI: 10.1371/journal.pone.0235280
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of DS-1-like rotavirus infection in Thai adults between 2016 and 2019

Abstract: Rotavirus infection is the most common cause of viral diarrhea in infants and young children but uncommon and usually asymptomatic in adults. In the winter of 2017-2018, a largescale outbreak of rotavirus in both children and adults was reported in Thailand. The current study focused on the prevalence, genotyping, and molecular characterization of rotavirus infections in Thai adults from July 2016 to December 2019. In 2,598 stool samples collected from adult residents of Bangkok (aged #x2265; 15 years) with ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 52 publications
0
20
0
2
Order By: Relevance
“…The incidence of rotavirus diarrhea in adults has been reported ranging from 2 to 22% of gastroenteritis cases in numerous countries [ 48 , 49 ]. In the present study, the incidence (12.3%) of RVA was higher than that in Thai adults (8.7%) [ 50 ]. It is suggested that rotavirus gastroenteritis in adult population should be also prevented by any intervention in China.…”
Section: Discussionmentioning
confidence: 53%
“…The incidence of rotavirus diarrhea in adults has been reported ranging from 2 to 22% of gastroenteritis cases in numerous countries [ 48 , 49 ]. In the present study, the incidence (12.3%) of RVA was higher than that in Thai adults (8.7%) [ 50 ]. It is suggested that rotavirus gastroenteritis in adult population should be also prevented by any intervention in China.…”
Section: Discussionmentioning
confidence: 53%
“…Among the 2,001 stool samples obtained from infants and young patients with AGE over a 4-year study period (January 2016 to December 2019), 301 samples (15.0%) tested positive for RVA. Interestingly, there was a large-scale outbreak of RVA infection in both children and adult between December 2017 and March 2018 ( Chansaenroj et al, 2020 ). The highest frequency of RVA infection in this study occurred in children aged 0–24 months (48.2%), which corresponded to data from a previous study in Mexico, in which almost all of the children by 2 years of age had been infected at least once, and more than two-thirds had experienced at RVA least twice, and more than 10% had experienced five infections ( Velázquez et al, 1996 ).…”
Section: Discussionmentioning
confidence: 99%
“…The primers VP6-F (5′ GACGGVGCRACTACATGGT 3′) and VP6-R (5′ GTCCAATTCATNCCTGGTGG 3′) a 379-bp region corresponding to nucleotides 747–1,126 of the VP6 gene. Cycling parameters were reverse transcription at 50 °C for 30 min, initial denaturation at 95 °C for 15 min, 45 cycles of denaturation at 94 °C for 15 s, annealing at 60 °C for 30 s, and extension at 72 °C for 30 s. Melting curve analysis was explored from 60 °C to 95 °C with 1 °C increments to determine the specificity of the reactions ( Kang et al, 2004 ; Chansaenroj et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Russia, this genotype combination was detected previously in the Siberian region [28]. Viruses with the G8P [8] genotype combination have been detected in people in Africa and Asia, where they cause disease not only in children, but also in adults [29,34]. Viruses with the G9P [4] combination are widespread in Asia and South America, though sometimes they are detected in Europe [35].…”
Section: Discussionmentioning
confidence: 78%